2008
DOI: 10.1890/07-0471.1
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Induced Defenses to Herbivory in Above- And Belowground Plant Tissues

Abstract: A recent surge in attention devoted to the ecology of soil biota has prompted interest in quantifying similarities and differences between interactions occurring in above- and belowground communities. Furthermore, linkages that interconnect the dynamics of these two spatially distinct ecosystems are increasingly documented. We use a similar approach in the context of understanding plant defenses to herbivory, including how they are allocated between leaves and roots (constitutive defenses), and potential cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
238
4
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(260 citation statements)
references
References 111 publications
(126 reference statements)
10
238
4
8
Order By: Relevance
“…Taken together, changes in tannins in roots and leaves may contribute to the variable performance of Bikasha above-ground adults and below-ground larvae, and their interactions. A growing body of evidence indicates that induced defence to above-ground herbivory may be substantially different from that to below-ground herbivory [14,[31][32][33]. The different tannin responses in above-ground and belowground tissues may also reflect an asymmetric induction and associated transportation in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, changes in tannins in roots and leaves may contribute to the variable performance of Bikasha above-ground adults and below-ground larvae, and their interactions. A growing body of evidence indicates that induced defence to above-ground herbivory may be substantially different from that to below-ground herbivory [14,[31][32][33]. The different tannin responses in above-ground and belowground tissues may also reflect an asymmetric induction and associated transportation in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Although facilitative, there remained a degree of asymmetry in the interaction, with weevils exerting a much greater effect on aphid abundance than vice versa. While feeding facilitation has been found above-ground [17], positive non-reciprocal effects of above-ground herbivores on belowground herbivores are generally scarce (reviewed in [18]), and only one other study [5] has, to our knowledge, demonstrated reciprocal facilitation between above-and below-ground herbivores. In that case, the abundance of wireworms (Agriotes spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Light has been shown to mediate the synthesis and activation of β-carbolines, a set of phytochemicals derived from tryptophan, which includes brevicolline (Downum, 1992). Regarding herbivory, the induction of toxic compounds has been much more studied in plant-insect systems (Kessler & Baldwin, 2002;Castells et al, 2005;Chen, 2008;Kaplan et al, 2008) than in plantmammal systems (Huntzinger et al, 2004;Zinn et al, 2007), although the occurrence of mechanisms of cross-resistance (defences induced by a particular herbivore being effective against other herbivores that consume the same plant) are assumed (Kessler & Baldwin, 2004). In plant-mammal systems, research has particularly addressed the loss of plant digestibility caused by the synthesis of defences against grazing/ browsing (such as phenolic or silica-based compounds, Massey et al, 2007), or it has focused on animals rather than plants, analysing the mechanisms developed by mammals to avoid or tolerate toxicity (Torregrossa & Dearing, 2010).…”
Section: Introductionmentioning
confidence: 99%